Cusp-singularity-enhanced Coriolis effect for sensitive chip-scale gyroscopes - Sen Zhang; Dingbang Xiao; Fei Wang; Ran Huang; Lei Yu; Ning Zhou; Kaixuan He; Xuezhong Wu; Franco Nori; Hui Jing; Xin Zhou (Nature, 2026)
Abstract Gyroscopes, as fundamental inertial sensors, are crucial for rotation measurements in the consumer electronics, automotive and aerospace industries, with the most widely used kind relying on the Coriolis effect 1–6 . The chip-scale Coriolis vibratory gyroscopes (CVGs) show reduced size, weight and cost 1,2 but have far lower performance than traditional macroscale CVGs 3–6 , as the weak intrinsic Coriolis factor sets a fundamental limit on scaling the sensitivity against the inherently louder Brownian noise in microchips compared with the macroscale ones. Here, to overcome this physical limit, we propose and experimentally demonstrate the use of third-order singularities lying within cusp catastrophes in the phase-tracked oscillations of an on-chip CVG to facilitate a cubic-root scaling of the Coriolis-effect-induced frequency modulation. Using this effect, we achieve a three-orders-of-magnitude enhancement in the Coriolis factor, yielding a 253-fold improvement in the signal-to-noise ratio and a 297-fold increase in precision. Moreover, the cusp singularity enables a previously unattainable ultrasensitive phase-modulated sublinear measurement, achieving record signal-to-noise ratio performance for silicon-chip gyroscopes. These findings not only provide revolutionary advancements in gyroscope technologies, by filling the gap in observing and controlling the singularity-enhanced Coriolis effect, but also shed new light on other ultrasensitive sensing applications.